Research on conflict resolution control strategy for vehicles and aircrafts on airport surface - Haiyan Zhang; Jian Zhang; Feng Zhu; Pinzheng Qian; Han Jiang; Xuejian Yao (Urban Lifeline)
Abstract Currently, the driving of special vehicles at airports mostly relies on manual decision-making and management, resulting in frequent conflicts between vehicles and aircrafts, which bring certain risks and hidden dangers. To mitigate the risks of vehicle-aircraft conflicts during the operation process on the airport surface, this paper identifies the conflict areas based on airport surface operational rules and establishes driving models for both vehicles and aircrafts. An optimized First-Come-First-Served (FCFS) conflict resolution control strategy was designed to resolve conflicts, and SUMO software was used to make the simulation based on the data from a certain international airport in China. Results show that without control, 96 vehicle-aircraft conflict incidents occurred. After the FCFS-based control strategy was applied, all conflicts were resolved, and the time for vehicles and aircraft passing through conflict areas was reduced from 28.52 s to 24.64 s, demonstrating the effectiveness of the conflict resolution strategy in terms of conflict reduction and energy savings.